Influence of beginning college type on post secondary educational achievement: a matched pairs study - Vance, Joanna, author; Davies, Timothy G., advisor (Colorado State University. Libraries, 2009)
The purpose of this study was to gather more information about the influence of beginning higher education at a two-year college versus beginning at a four-year college on a student's educational achievement. The three outcomes of interest were: (1) whether a student remains continuously enrolled throughout college; (2) total number of college credits a student completes; and (3) highest degree, if any, a student obtains. In order to compare students who began at two-year colleges with their peers who began at four-year colleges, students were matched on the following six variables: (1) gender, (2) ethnicity, (3) mother's highest level of education, (4) father's highest level of education, (5) total family income during the student's eighth grade year, and (6) the student's own predictions of how far they will go in post secondary education, made while seniors in high school. The study used data collected by the National Educational Longitudinal Study of 1988 (NELS:88). The study supported previous literature, finding that students who begin at two-year schools are 48% more likely to complete less than one year of full-time enrollment than are their four-year peers and are 42% less likely to stay continuously enrolled over their college experience than are their four-year peers. The study also found that students who begin at four-year schools are 46% more likely to obtain a bachelor's degree than their two-year peers. For all three outcome variables of interest those students who began at four-year colleges achieved more academically than their matched peers who began at two-year colleges. When two students who are very similar in terms of gender, ethnicity, parents' level of education, socioeconomic status and self perceived future achievement begin their education at different colleges-one a four-year school and the other a two-year school-the four-year attendee consistently will achieve more academically. This information is important and relevant to students, parents, researchers, and policymakers alike.
Keywords: achievement; beginning college type; matched pairs; NELS:88; postsecondary; community college education; higher education